KEANEKARAGAMAN CAPUNG DI TAMAN WISATA ALAM DANAU SICIKEH–CIKEH DESA LAE HOLE KECAMATAN PARBULUAN KABUPATEN DAIRI SUMATERA UTARA - Sofiana Gultom; Kartika Manalu; Efrida Pima Sari Tambunan (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
This study aims to determine the type, abundance, and frequency of dragonflies (Odonata) in the Lake Sicikeh-cikeh Nature Tourism Park, Lae Hole Village, Parbuluan District, North Sumatra Province. This research was conducted in November 2019. This research used the Exploration method. Observations were made at three stations. Data obtained from the field are processed manually, after the data is collected, processed, then presented in the form of a table and described descriptively. The results showed an abundance of dragonflies in Lake Sicikeh-Cikeh Nature Tourism Park categorized as moderate diversity. The highest abundance of dragonflies is found in the species of Neurothemis fluctuans Fabricius with a relative abundance of 37.17%. The highest relative frequency is found in species of Pseudagrion microcephalum Rambur, Neurothemis fluctuans Fabricius, and Rhodothemis rufa Rambur with a relative abundance value of 15%.Keywords:  diversity, dragonflies, lake sicikeh-cikeh nature tourism park